Effect of Non-Fumigant Nematicides on Reproduction of Recently Detected Meloidogyne Species in Georgia Under Greenhouse Conditions in Tomato - Nabin Poudel; Luis Torres; Richard F. Davis; Ganpati B. Jagdale; Theodore McAvoy; Intiaz A. Chowdhury (Horticulturae)
Root-knot nematodes (Meloidogyne spp.; RKNs) are among the most destructive soil-borne pathogens affecting tomato production. Recently, aggressive species such as M. enterolobii, M. floridensis, and M. haplanaria have been reported in several tomato fields across the southern United States. Host resistance in tomato, effective against commonly prevalent M. incognita, is ineffective against these emerging species, making chemical nematicides the primary management approach. However, studies on the efficacy of chemical nematicides on these emerging RKN species remain limited. This study evaluated the efficacy of four non-fumigant nematicides—fluazaindolizine, fluensulfone, fluopyram, and oxamyl—on the reproduction of these emerging species and M. incognita. Fluensulfone consistently suppressed nematode reproduction by over 90.0% across all species. Fluopyram reduced reproduction by over 50.0% in most species but was less effective against M. enterolobii, with suppression of only 24.3%. Similarly, fluazaindolizine suppressed egg counts by more than 50.0% across all species except M. enterolobii, where it suppressed only 41.1%. Oxamyl suppressed egg counts in M. floridensis and M. incognita by more than 50.0%, but reductions in M. enterolobii and M. haplanaria were lower at 23.2% and 38.7%, respectively. These results highlight species-specific differences in nematicide efficacy and provide a crucial baseline for future research for the management of specific RKN species.